Physical fitness assessment in wheelchair basketball: A mini-review - Petrigna, Luca; Pajaujiene, Simona; Musumeci, Giuseppe (Frontiers in Sports and Active Living, 2022)
Introduction. Wheelchair basketball (WB) is a Paralympic sport ideated for people with motor disabilities and the research on this topic still requires attention. It is fundamental to evaluate physical fitness characteristics to plan and monitor the training with appropriate tolls and a standardized routine. A standard operating procedure is a document that makes the test battery replicable. Consequently, the objective of the present study was to review the literature on physical fitness assessment in WB players and to create a standard operating procedure. Methods. Studies were collected in different databases and, after the screening process, data were discussed narratively. Results. Only 18 articles met the eligibility criteria. The test batteries presented similarities in different studies. Conclusion. The standard operating procedure consists in 10 min warm-up followed by handgrip evaluation (only if the instrument is available); 20 m sprint test; maximal pass; modified push-up; back scratch test, and the Yo-Yo intermittent recovery test adapted test Version 1.